The content and structure of regional masterplans: As exemplified by the plan for the Munich-West region - Albert, Stephanie (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Under section 9 para. 6 of the German Federal Regional Planning Act (theRaumordnungsgesetz — ROG) it is possible for a single plan to perform the functions both of a regional plan and of a joint (i.e. inter-authority) masterplan (or “preparatory land-use plan” in this case a regional masterplan). In providing this option, the legislature was reacting to the requirements of more efficient planning and for closer co-ordination of the various tiers of planning. In this article the regional masterplan is discussed as a new instrument of regional and land-use planning. Within this context the article identifies normative planning elements of regional masterplanning, which are exemplified in more concrete terms by reference to the Munich region. The article discusses such issues as the matter to be included in the textual component of the plan, as well as the cartographic representation of the regional masterplan. It concludes by pointing out a number of problem areas in implementation and discussing attempts at finding solutions.